2010
DOI: 10.1249/mss.0b013e3181b5419a
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and Exercise Prevent Excess Weight Gain in Overweight Pregnant Women

Abstract: NELIP reduces the risk of excessive pregnancy weight gain with minimal weight retention at 2 months postpartum in OW and OB women. This intervention may assist OW and OB women in successful weight control after childbirth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
144
4
18

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(174 citation statements)
references
References 30 publications
4
144
4
18
Order By: Relevance
“…Although shifting the occurrence of a large for gestational age baby to a normal range has benefits for maternal outcomes, elevated birth weight is not always observed and therefore cannot always be assumed in human studies or animal models of maternal over-nutrition. Indeed, birth weight data in the above mentioned studies [24][25][26][27] and our recent review of maternal high-fat feeding and offspring development show birth weight is often similar between offspring groups or in fact lower in offspring of obese mothers compared with controls. 28 A major limitation of human studies is the degree to which a mechanistic understanding may be achieved without invasive procedures in children.…”
Section: Maternal Obesity And/over-nutrition Predisposes Offspring Tomentioning
confidence: 97%
See 1 more Smart Citation
“…Although shifting the occurrence of a large for gestational age baby to a normal range has benefits for maternal outcomes, elevated birth weight is not always observed and therefore cannot always be assumed in human studies or animal models of maternal over-nutrition. Indeed, birth weight data in the above mentioned studies [24][25][26][27] and our recent review of maternal high-fat feeding and offspring development show birth weight is often similar between offspring groups or in fact lower in offspring of obese mothers compared with controls. 28 A major limitation of human studies is the degree to which a mechanistic understanding may be achieved without invasive procedures in children.…”
Section: Maternal Obesity And/over-nutrition Predisposes Offspring Tomentioning
confidence: 97%
“…Increasing attention towards interventions that may be used to improve maternal health could, therefore, impact substantially on offspring health both in the short and long term. A number of early reviews, 19,[22][23][24][25] in addition to two recent studies, 26,27 have identified altering maternal carbohydrate intake as well as maternal physical activity levels as potential strategies for positively regulating maternal weight gain and offspring birth weight among other pregnancy outcomes. However, longitudinal studies that describe the potential long-term benefits of these interventions for offspring health are lacking.…”
Section: Maternal Obesity And/over-nutrition Predisposes Offspring Tomentioning
confidence: 99%
“…Recent findings from intervention studies show that gestational weight gain can be kept at a healthy level in both healthy-weight women (BMI 18.5-24.9) [6] and overweight women [11]. In other words, excess gestational weight gain is preventable [12].…”
Section: Introductionmentioning
confidence: 99%
“…Esto ocurre desde la semana 6-8 de gestación, alcanzando el valor máximo al final del segundo trimestre, donde se estabiliza 10 . La adaptación estructural del corazón necesaria para asumir este mayor volumen sanguíneo se traduce, en condiciones normales, en un incremento del diámetro telediastólico del ventrículo izquierdo (DTDVI) y mayor distensibilidad del ventrículo, con lo que se consigue el necesario aumento del gasto cardiaco sin elevar las presiones intracavitarias ni la presión sistémica 2 .…”
Section: Cambios Cardiovasculares Durante El Embarazounclassified
“…En este sentido, son muchos los estudios que informan de posibles mejoras en la salud de estas gestantes a través de la práctica regular de ejercicio físico moderado durante el embarazo [3][4][5][6][7][8][9][10] .…”
Section: Introductionunclassified